RADIOACTIVITY LEVELS IN SOME MUSHROOM SPECIES COLLECTED FROM MACEDONIA AND CONSEQUENT DOSES - Angeleska, Aleksandra; Crceva-Nikolovska, Radmila; Dimitrieska Stojkovikj, Elizabeta; Blagoevska, Katerina; Stojanovska-Dimzoska, Biljana; Uzunov, Risto; Poposka - trenevska, Vasilka (University of East Sarajevo, Faculty of Agriculture, 2022)
Mushrooms are bioindicators in the environment that accumulate radionuclides, therefore they can pose a radiological threat. In the Republic of Macedonia, mushrooms are widely consumed as a part of the diet, for this reason their radiological control is required. In this research, the activity concentrations in different types of mushrooms (Boletus edulis, Marasmius oreades, Morchela conica, Lactarius deliciosus) were determined. The mushrooms were collected from six different locations in the Republic of Macedonia, and information on the radiation dose for the general population were obtained with this measurement. The analyses were performed by means of HPGe gamma spectrometry, i.e. an instrument - gamma spectrometer (Canbera Packard) with a high purity germanium detector. The obtained spectra from the measurement were analyzed by using the GENIE 2000 program. On the basis of the performed tests, the mean values for the activity concentrations in the mushrooms were as follows 41.9±1.2 Bq kg − 1 for 226Ra, 40.3±1.8 Bq kg − 1 for 232Th, 83.75±6.2 Bq kg − 1 for 40K, and 2.34±0.24 Bq kg − 1 for 137Сs. The mean value of the radiation risk index Heks is lower than the maximum allowed value which is <1 for Heks. The value of the radium equivalent activity Raeq is below the maximum recommended limit, i.e. 370 Bq kg-1. Significant variations were not observed in regard to the activity concentrations of 137Cs and 40K in the same mushroom species from different sampling points. High activity concentrations of 137Cs activity were not detected in any of the mushrooms. The researches in this study show that all mushroom samples pose no biological threat, i.e. it was found that the analyzed radionuclides do not pose a health risk and the levels are below the international standards.
Keywords: mushrooms, gamma-ray spectrometry, natural radioactivity, food safety.